Lost in Transmission? John Berger and the Origins of Ways of Seeing (1972). (24th August 2020) - Conlin, Jonathan
Abstract: The documentary series Ways of Seeing was broadcast on BBC television in January 1972. Directed by Mike Dibb and presented by the marxist critic John Berger, the series addressed the canon of western art history as well as contemporary consumer culture. The conspicuous use of cross-cutting and music along with Berger's emphatic 'talking-head' delivery were employed to dispel the aura enveloping 'original' artworks, and reveal the technologies by which art historians, curators and advertising agencies shored up a capitalist, western, male social order. The series and its associated book were canonical for the nascent disciplines of media and culture studies. Drawing on scripts and other materials from the BBC, Berger and Dibb archives, this essay explains how the four episodes were conceived and executed. It places the series in the context of Berger's prior activity as artist, art critic, presenter and author, noting the influence of Frederick Antal, Walter Benjamin and others. It concludes that Berger's charisma and the mastery of the relatively new technology of colour television displayed by the series undermined its intent: rather than encouraging viewers to use images in framing their own personal narratives, its message was consumed as an invitation to view all images in political terms.